Apically Extruded Debris during Instrumentation using Different Engine Driven File Systems: A Comparative In Vitro Study - AlChalabi, Ashraf; Alkhalidi, Emad; Chakmakchi, Makdad (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM: The aim of the present study was to evaluate and compare the amount of apically extruded debris using three engine driven systems. METHODS: Sixty mandibular premolars with single root were used. The samples were divided into three groups with 20 teeth for each group: group 1 Neolix Neoniti A1 (25, 0.08), group 2 WaveOne GOLD Primary (25.07, red), and group 3 Protaper Next (PTN), using X1 (017/0.04), X2 (025/0.06) files. All files were used to prepare the root canals according to manufacturer instruction. Root canal preparation for each group was done according to manufacturer instructions using 16:1 gear reduction hand piece powered by a torque controlled electric motor. Debris collection was made using apparatus described by Myers and Montgomery. The extruded debris weight was measured by subtracting the weight of the empty Eppendorf tubes from the weight of the debris containing tubes results were statistically analyzed. RESULTS: One-way analysis of variance test revealed that there was statistically significant differences between all the three groups being tested (p < 0.001) showed that apical extrusion of the debris of WaveOne Gold was the least followed by Neolix Neoniti and finally PTN which showed the most apical extrusion of debris with a significant difference between all groups. CONCLUSIONS: WaveOne Gold was found to be the least apical extruded debris system among all groups.